Improving prioritization processes for clinical practice guidelines: new methods and an evaluation from the National Heart Foundation of Australia - Brooke Atkins; Tom Briffa; Cia Connell; Amanda K. Buttery; Garry L. R. Jennings (BMC, 2023)
Abstract Background Releasing timely and relevant clinical guidelines is challenging for organizations globally. Priority-setting is crucial, as guideline development is resource-intensive. Our aim, as a national organization responsible for developing cardiovascular clinical guidelines, was to develop a method for generating and prioritizing topics for future clinical guideline development in areas where guidance was most needed. Methods Several novel processes were developed, adopted and evaluated, including (1) initial public consultation for health professionals and the general public to generate topics; (2) thematic and qualitative analysis, according to the International Classification of Diseases (ICD-11), to aggregate topics; (3) adapting a criteria-based matrix tool to prioritize topics; (4) achieving consensus through a modified-nominal group technique and voting on priorities; and (5) process evaluation via survey of end-users. The latter comprised the organization's Expert Committee of 12 members with expertise across cardiology and public health, including two citizen representatives. Results Topics (n = 405; reduced to n = 278 when duplicates removed) were identified from public consultation responses (n = 107 respondents). Thematic analysis synthesized 127 topics that were then categorized into 37 themes using ICD-11 codes. Exclusion criteria were applied (n = 32 themes omitted), resulting in five short-listed topics: (1) congenital heart disease, (2) valvular heart disease, (3) hypercholesterolaemia, (4) hypertension and (5) ischaemic heart diseases and diseases of the coronary artery. The Expert Committee applied the prioritization matrix to all five short-listed topics during a consensus meeting and voted to prioritize topics. Unanimous consensus was reached for the topic voted the highest priority: ischaemic heart disease and diseases of the coronary arteries, resulting in the decision to update the organization's 2016 clinical guidelines for acute coronary syndromes. Evaluation indicated that initial public consultation was highly valued by the Expert Committee, and the matrix tool was easy to use and improved transparency in priority-setting. Conclusion Developing a multistage, systematic process, incorporating public consultation and an international classification system led to improved transparency in our clinical guideline priority-setting processes and that topics chosen would have the greatest impact on health outcomes. These methods are potentially applicable to other national and international organizations responsible for developing clinical guidelines.